2019
DOI: 10.1080/13552600.2019.1581282
|View full text |Cite
|
Sign up to set email alerts
|

Differential predictors of intimate partner sexual coercion versus physical assault perpetration

Abstract: The current study attempted to strengthen existing literature regarding predictors of perpetrating intimate partner sexual violence to determine if there are unique predictors of sexual violence that differentiate it from physical abuse. It was hypothesised that men's controlling, dominant and jealousy behaviours, and verbal aggression would significantly predict increased intimate partner sexual coercion and physical assault perpetration. These predictors were expected to be more predictive of sexual coercion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In studies from North and Latin America the association was particularly strong for physical and sexual IPV and RJ. In several US studies, male RJ was found to be associated with physical IPV [59,62], sexual IPV [67] and physical or sexual IPV [60], while mutual RJ by both partners was found to be associated with physical IPV, and this association was greater among reciprocally violent couples [61].…”
Section: Ipv Outcomes and Associations With Infidelity Or Rjmentioning
confidence: 98%
See 2 more Smart Citations
“…In studies from North and Latin America the association was particularly strong for physical and sexual IPV and RJ. In several US studies, male RJ was found to be associated with physical IPV [59,62], sexual IPV [67] and physical or sexual IPV [60], while mutual RJ by both partners was found to be associated with physical IPV, and this association was greater among reciprocally violent couples [61].…”
Section: Ipv Outcomes and Associations With Infidelity Or Rjmentioning
confidence: 98%
“…Emotional jealousy assessed how "upset" partners would feel in response to various jealousy-evoking situations. Behavioural jealousy measured how often partners engaged in various protective behaviours (i.e., verbal attack of possible relationship competitors) and detective behaviours (i.e., going through their partner's belongings) [67].…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it was described [44] that one of the significant predictors of sexual coercion and physical violence are attitudes of men who like to be in control of the relationship and their partner. One of the components of this type of relationship is jealousy, which has been nominated as romantic jealousy which is different than other type of jealousy like for example sibling rivalry.…”
Section: Discussionmentioning
confidence: 99%
“…A community-based study reported that 15% of men and women had, at some time, been subjected to physical violence by a jealous partner (Mullen and Martin, 1994) and it has been suggested that up to 20% of all murders are contributed to by romantic jealousy (White and Mullen, 1989). Significant associations between jealousy and intimate partner sexual coercion have also been reported in men (Snead and Babcock, 2019). The incidence of pathological romantic jealousy is estimated to be 0.5-1% of the population (Soyka and Schmidt, 2011) although only the delusional form is recognized as a disorder under DSM V as a sub-category of delusional psychosis (APA, 2013).…”
Section: Introductionmentioning
confidence: 99%